Biopesticides for crop growth and crop protection (The Journal of Plant Protection Sciences, 2021)
Tablets made of garlic bulbs and allamanda leaves tremendously increased germination and reduced damping-off, seed rot, seedling blight and tip over of vegetables (egg-plant, tomato, chilli) in the nursery and leaf blight, anthracnose, fruit rot, root knot and leaf curl/mosaic of tomato and carrot in the field. Aqueous solution of garlic and allamanda tablet sprayed at 1:1, 1:2, 1:3, 1:3, 1:4, 1:5 conc. increased seed germination by 45-60%, completely eliminated damping-off, seedling blight and tip over and increased seedling vigour by 22-50%. The tablets retained the similar range of action over aging up to 90 days. Both garlic and allamanda tablets displayed similar inhibitory action against damping-off and seedling blight pathogens, Phomopsis vexans and Sclerotium rolfsii. In the field, garlic and allamanda spray reduced leaf blight severity by 84-86% and fruit rot by 91%. Severities of nematode and virus infection were also reduced significantly with allamanda spray. Active compounds in allamanda leaves have been separated and identified. Formulated trichoderma effectively controlled soil-borne diseases including root-knot nematode. Mahogany oil spray reduced infestation of stem borer, leaf hoppers of rice; shoot & fruit borer of brinjal and fruit flies of vegetables. Biopesticides (formulated trichoderma) and bio-agents (bracon, trichogramma, ladybird beetle) and sex pheromone are in the pipeline for commercial use.
Keywords: Garlic and allamanda tablets; biopesticides; bioagents; vegetable diseases